Vzaimosvjaz' special'noj fiziceskoj podgotovlennosti sportsmenov so strukturoj sorevnovatel'noj dejatel'nosti v plavanii - Petryaev, A. V.; Litvinov, A. V.; Rybyakova, T. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
To understand the principles of building up a long-term training for the young athletes, and the effective selection of the tools and methods in the process of the long-term individual physical preparation, the knowledge of the correlation between the development level of special physical qualities of swimmers and assessment of their competitive activity is of great importance. The purpose of this study was to determine the relationship between the special physical preparedness of swimmers and the structure of the competitive activity. Research objectives: to identify informative tests of special physical preparedness of swimmers at various stages of the long-term training; determine their correlation with the structure of the competitive activity. As a result of the studies, informative tests of the swimmers' special physical preparedness on land and in water were identified, and their relationship with the structure of competitive activity was determined. The scientific novelty of the work is the determination of the relationship of the proposed battery of informative tests to assess the special physical preparedness of the swimmers with the structure of competitive activity in swimming. The practical significance lies in the development of the methodology for testing the level of special physical efficiency of swimmers through tests at the stages of long-term training.